“Girls need sex education more”: Gendered views of kindergarten teachers on children’s sex education - Septriani Renteng; Valen Fridolin Simak; Andi Buanasari (Universitas Ahmad Dahlan, 2026)
Preschool-aged children are vulnerable to sexual violence due to limited knowledge of sexual concepts, body autonomy, and personal boundaries. Early sex education is essential to strengthen children’s protective knowledge and help-seeking behaviors. In Indonesia, however, sex education for early childhood is often constrained by social taboos, limited teacher training, and insufficient instructional resources. Teachers play a central role in delivering age-appropriate sex education in schools, yet their perceptions and experiences remain underexplored. Therefore, this study aimed to explore kindergarten teachers' perceptions of sex education for preschool-aged children, including their understanding of sex education concepts, implementation challenges, and expectations for effective delivery. A qualitative study using a descriptive-phenomenological approach was conducted from August to September 2024 in Manado City. Purposive sampling was employed to recruit 15 kindergarten teachers as main informants and 7 preschool-aged children as supporting informants for data triangulation. Data were collected through in-depth interviews and participant observation. All interviews were audio-recorded, transcribed verbatim, and analyzed thematically. Two main themes emerged: (1) sex education for preschool-aged children and (2) challenges and expectations of teachers in conducting sex education. Teachers generally understood sex education as teaching body autonomy, private body parts, gender identity, and safe versus unsafe touch. However, perceptions differed regarding the appropriate age to introduce sex education and whether girls should receive greater emphasis than boys. Children's growth, attention spans, training, and teaching medium were challenges. Teachers stressed interactive methods and engagement with parents, health workers, and government agencies. Early childhood sex education is heavily influenced by teachers' expertise, challenges, and expectations. Effective and sustainable early sex education requires teacher competency, age-appropriate resources, and multi-stakeholder collaboration.